Peran Paus Fransiskus Dalam Pemulihan Hubungan Diplomatik Amerika Serikat dan Kuba - S, Sheila; Albayumi, Fuat; Hasan, Muhammad Nur (University of Jember, 2017)
Abstract Diplomatic relations between the United States of America and Cuba that had been cut off for 55 years were a phenomenon that attracted the international community’s attention, particularly from the Vatican. In seeking the rapprochement of diplomatic relations between the United States and Cuba, three Popes played a role in this issue i.e. Pope John Paul II, Pope Benedict XVI and Pope Francis. Pope John Paul II and Pope Benedict XVI were, in fact, unsuccessful in realizing the rapprochement in the United States of America and Cuba relations. However, Pope Francis was significantly successful in the recovery process of the relationship. This research will explain the role of Pope Francis in the the rapprochement of diplomatic relations between the United States and Cuba. The research used qualitative, descriptive method and the data used were obtained through literatures with various relevant resources. The results showed that the role of Pope Francis as a mediator, facilitator and religious leader managed to make the two countries to establish a communication and discussion to find solutions together and to influence people from both countries to support each government for the realization of the rapprochement of diplomatic relations between the United States of America and Cuba. Keywords